INTERPRETER TRAINING: LANGUAGE, CULTURE OR MORE? COURSE DESIGN: THE EXPERIENCE OF THE UNIVERSITY OF CENTRAL LANCASHIRE, PRESTON, UK - Mouallem, Summer (European Scientific Journal, ESJ, 2015)
How important is it to include formal training on ethics and cross cultural issues within interpreting and translation training courses? The role of interpreters has been debated for many years by scholars where some see their role as mere people who transfer the spoken message from the source to the target language, with no omissions or additions. While others see the role of interpreters extending beyond the mere transfer of words and messages; they see messages as utterances loaded with spoken and unspoken cultural essences that need to be transferred too. By looking at some training courses available in the UK, it became clear that there is a need to teach the students a little more than just the required techniques and skills in interpreting and coping with interpreting difficulties. Shortfalls seen in courses were studied closely and were included in the design of the course. Taboo varies from one culture to another; what is seen as right (ethical) in one society may be seen as wrong (unethical) in another. How we deal with ethical or unethical issues depends on our own built in or acquired ethics and this may be reflected in our professional lives too. However, in our capacity as professionals, we must be seen as unbiased and we must not allow our own prejudices colour our work; this is not easy when we consider this has been growing within us since birth practically and hence re-training ourselves to become impartial in issues that are cultural must be an essential part of training. Acting ethically does not mean doing what the society describes as right: the law can incorporate ethical standards to which people subscribe but these laws can deviate from what is normatively ethical. Ethics are categorised as Deontological ethics or duty-based ethics (non- consequential)l; this means: • Do the right thing • Do it because it is the right thing to do • Avoid them because they are wrong. And then we have consequential ethics ("The ends justify the means", this means: • What sort of consequences count as good consequences? • Who is the primary beneficiary of moral action? • How are the consequences judged and who judges them ? This paper intends to show the steps taken in the design of the content of the interpreting and translation modules and the different angles used to ensure optimum preparation of future interpreters and translators. It will aim to show the problems and dilemmas faced when designing matters such as cultural and ethical matters where no two people can always agree but where it is essential we try and agree; it will show how no global consensus has been reached regarding what is right or wrong but yet it is necessary that we find common ground in order to move forward. The consequences of not doing so can be dire and this issue should not be ignored within our teaching institutions or by our practising colleagues.